BENTUK DAN ISI MANTRA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Mantra (magic formula) is a speech that invites an inscrutable power to heal, to expel ghost, ask rain, deliver accident, etc. Based on poetic principles, mantra is structured from words order element such as poetry like rhyme, song